Firms' intellectual property ownership aggressiveness in university–industry collaboration projects: Choosing the right governance mode - Oliver Gretsch; Frank Tietze; Alexander Kock (Creativity and Innovation Management, 2020)
Intellectual property (IP) ownership aggressiveness constitutes an organization's strategic stance that prioritizes its IP protection. An organization thus pursues a rigid approach to protect its background IP and strives for exclusive ownership of the foreground IP that results from collaborative projects. This paper investigates how firms' IP ownership aggressiveness influences university–industry collaboration (UIC) project success and examines if the relationship is contingent on the governance modes that firms employ in UICs, especially the intensity of contract formality and shared governance. Analysing survey data from UIC projects of medium-sized to large firms covering four industries, we find that the levels of contract formality and shared governance moderate the effect of firms' IP ownership aggressiveness on project success. Strong contract formality leads to a negative relationship between firms' IP ownership aggressiveness and UIC project success. Conversely, if firms apply strong shared governance, the relationship between IP ownership aggressiveness and UIC project success is positive. Given firms' strategic approach to protect background IP and claim ownership of foreground IP, these results have implications for UIC managers when selecting governance modes to best support UIC project success.
Keywords: 330